Hilfsmittelversorgung sehbehinderter Menschen am Arbeitsplatz - Lammert, Kai; Denninghaus, Erwin; Rohrschneider, Klaus (Der Ophthalmologe, 2018)
The provision of aids for occupational use with partially sighted and blind people is not a measure for the necessary care but for an optimal work performance to secure the long-term occupational participation. This objective requires a significantly expanded consultation, which includes the occupational requirements at the specific workplace. The costs are not usually borne by the statutory health insurance but by another social insurance agency depending on the individual case. In this article several aids are presented in an occupational context, as well as the procedure for provision.
First Online: 21 December 2017
Gesehen am 04.11.2019